Wound Infection in Gynecologic Surgery - Aparna A. Kamat; Leo Brancazio; Mark Gibson (Hindawi Limited, 2000)
Objective: We sought to determine the wound infection rate among patients undergoing elective gynecologic surgery at a single tertiary care center and to determine the predictive value of various factors that contribute to infection. We further investigated the adequacy of hospital records in documenting infection rates as well as the timing of presentation of wound infections.